Applied Algebra, Algebraic Algorithms and Error-Correcting Codes
DOI: 10.1007/978-3-540-77224-8_9
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Sudan’s List Decoding for Order Domain Codes

Abstract: Abstract. We generalize Sudan's list decoding algorithm without multiplicity to evaluation codes coming from arbitrary order domains. The number of correctable errors by the proposed method is larger than the original list decoding without multiplicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Publication Types

Select...
2
2
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…First to see that (X 3 , X) is OWB we must show that HX rem G = X 3 X rem G for all H with lm(H) = X 3 . We have (16) no matter what are a 1 , . .…”
Section: Example 3 Consider the Idealsmentioning
confidence: 99%
See 1 more Smart Citation
“…First to see that (X 3 , X) is OWB we must show that HX rem G = X 3 X rem G for all H with lm(H) = X 3 . We have (16) no matter what are a 1 , . .…”
Section: Example 3 Consider the Idealsmentioning
confidence: 99%
“…Many papers deal with decoding of evaluation codes. Among these are [20], [6], and [16]. A study of the function µ on different families of semigroups Γ can be found in [5] and [34].…”
Section: Bibliographical Notesmentioning
confidence: 99%
“…In combination with a preparation step this will allow us to correct more errors. The idea of a preparation step comes from [10]. The improved information regarding the zeros is derived by strengthening results reported by Dvir et al in [6].…”
Section: An Interpretation Of the Guruswami-sudan List Decoding Algormentioning
confidence: 90%
“…Moreover, in [19], the authors also present a generalization of the well-known list-decoding algorithm of Reed-Solomon codes given by Guruswami and Sudan [13] for the case of Reed-Muller codes. Then, Olav and Matsumoto [9], generalized this algorithm to evaluation codes from arbitrary order domains, in particular for hyperbolic codes. For more information about list decoding for AG codes see [2].…”
Section: Introductionmentioning
confidence: 99%